2012
DOI: 10.3390/pharmaceutics5010023
|View full text |Cite
|
Sign up to set email alerts
|

Organic Nitrate Maintains Bone Marrow Blood Perfusion in Ovariectomized Female Rats: A Dynamic, Contrast-Enhanced Magnetic Resonance Imaging (MRI) Study

Abstract: This study investigated the effects of nitrate on bone mineral density (BMD) and bone marrow perfusion in ovariectomized (OVX) female rats, and also the effects of nitrate on in vitro osteoblastic activity and osteoclastic differentiation of murine monocyte/macrophage RAW 264.7 cells. Female Sprague–Dawley rats were divided into OVX + nitrate group (isosorbide-5-mononitrate, ISM, 150 mg/kg/ day b.i.d), OVX + vehicle group, and control group. Lumbar spine CT bone densitometry and perfusion MRI were performed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…These results demonstrated that alterations in microcirculation of the lumbar vertebral marrow had an influence on its BMD and intervertebral discal healthy status. Some studies had been conducted with an aim to prevent and cure osteoporosis 18 and discal degenerative disease 19 through maintaining the microcirculation perfusion to the bone marrow with drugs or cell therapy. These successful experimental therapeutics also supported our hypothesis that microcirculation perfusion dysfunction of the vertebral marrow is a cause leading to bone mass loss and intervertebral disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that alterations in microcirculation of the lumbar vertebral marrow had an influence on its BMD and intervertebral discal healthy status. Some studies had been conducted with an aim to prevent and cure osteoporosis 18 and discal degenerative disease 19 through maintaining the microcirculation perfusion to the bone marrow with drugs or cell therapy. These successful experimental therapeutics also supported our hypothesis that microcirculation perfusion dysfunction of the vertebral marrow is a cause leading to bone mass loss and intervertebral disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that alterations in microcirculation of the lumbar vertebral marrow had an influence on its BMD and the health of the intervertebral disc. Some studies had been done with drugs or cell therapy aimed at prevention and cure of osteoporosis 18 and DDD 19 through maintaining the microcirculatory perfusion to the bone marrow. These successful experimental therapeutics also supported our hypothesis that dysfunction of the microcirculatory perfusion of the vertebral marrow is a cause leading to loss of bone mass and intervertebral disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Osteoblast Proliferation and Viability Assays . The osteoblast proliferation and viability were measured using 5-bromo-2′-deoxyuridine (BrdU) [ 24 ] incorporation and MTT cell viability assay [ 19 , 25 ], respectively. Briefly, UMR-106 cells were seeded in DMEM with 10% v/v FBS.…”
Section: Methodsmentioning
confidence: 99%